Candidate Species for Florida Aquaculture: Hybrid Striped Bass, Morone saxatilis x Morone chrysops - Cortney L. Ohs; Christian L. Miller; R. LeRoy Creswell (EDIS)
FA155, a 9-page illustrated fact sheet by Cortney L. Ohs, Christian L. Miller, and R. LeRoy Creswell, describes these crosses between striped bass and white bass, commonly called sunshine bass and palmetto bass — geographical distribution and habitat, phases of production, pond, cage, and tank production, feeding, water quality, and marketing. Includes references. Published by the UF School of Forest Resources and Conservation Program for Fisheries and Aquatic Sciences, December 2008.